2001
DOI: 10.1073/pnas.231471298
|View full text |Cite
|
Sign up to set email alerts
|

Transient uptake of serotonin by newborn olfactory projection neurons

Abstract: A life-long turnover of sensory and interneuronal populations has been documented in the olfactory pathways of both vertebrates and invertebrates, creating a situation where the axons of new afferent and interneuronal populations must insert into a highly specialized glomerular neuropil. A dense serotonergic innervation of the primary olfactory processing areas where these neurons synapse also is a consistent feature across species. Prior studies in lobsters have shown that serotonin promotes the branching of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 40 publications
(56 reference statements)
0
50
0
Order By: Relevance
“…Towards this end, we have examined serotonin and nitric oxide as possible endogenous modulators of neurogenesis. Various in vitro and in vivo studies have shown that increases in serotonin levels result in an upregulation of neurogenesis in both the MPZ and LPZ of juvenile clawed lobsters (Benton and Beltz 2001a;Beltz et al 2001) and that decreases inhibit the branching of newborn projection neurons (Sullivan et al 2000). Furthermore, brain serotonin levels are under circadian control (Wildt et al 2004).…”
Section: Serotonin and Nitric Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…Towards this end, we have examined serotonin and nitric oxide as possible endogenous modulators of neurogenesis. Various in vitro and in vivo studies have shown that increases in serotonin levels result in an upregulation of neurogenesis in both the MPZ and LPZ of juvenile clawed lobsters (Benton and Beltz 2001a;Beltz et al 2001) and that decreases inhibit the branching of newborn projection neurons (Sullivan et al 2000). Furthermore, brain serotonin levels are under circadian control (Wildt et al 2004).…”
Section: Serotonin and Nitric Oxidementioning
confidence: 99%
“…These studies may ultimately reveal mechanisms by which other exogenous factors are translated into changes in neurogenesis. In this regard, it is important to note that we believe that serotonin may influence olfactory neuronal precursors both via release from fine fibers of the serotonergic dorsal giant neuron (DGN; Beltz et al 2001) and via a blood-born pathway. Recent in vitro studies in the clawed lobster demonstrate that neurogenesis in the LPZ is most sensitive to serotonin at very low (10 −10 M) concentrations (Fig.…”
Section: Serotonin and Nitric Oxidementioning
confidence: 99%
“…In the brain of the American lobster, reduced serotonin levels result in a decrease in neurogenesis among the deutocerebral local and projection neurons (clusters 9 and 10; Fig.·1) Beltz et al, 2001), while elevated serotonin levels result in an increased rate of neurogenesis (J. L. Benton, E. M. Goergen and B. S. Beltz, unpublished results). It is also known that a bundle of fine serotonergic fibers from the DGN terminate blindly in the region where new projection neurons are born in cluster 10 .…”
Section: Serotonin As a Regulator Of Neurogenesismentioning
confidence: 94%
“…In both vertebrate and invertebrate species, serotonin is a potent regulator of neurogenesis Daszuta, 1999, 2000;Benton and Beltz, 2001;Beltz et al, 2001;Jacobs, 2002;Radley and Jacobs, 2002;Malberg and Duman, 2003). In the brain of the American lobster, reduced serotonin levels result in a decrease in neurogenesis among the deutocerebral local and projection neurons (clusters 9 and 10; Fig.·1) Beltz et al, 2001), while elevated serotonin levels result in an increased rate of neurogenesis (J. L. Benton, E. M. Goergen and B. S. Beltz, unpublished results).…”
Section: Serotonin As a Regulator Of Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation